Long-Run Relationship between Islamic Financing Products and Banks’ Financial Performance - Dg Safrina Ag Budin; Syed Musa Syed Jaafar Alhabshi; Anwar Hasan Abdullah Othman; Rosle Mohidin (ResearchGate, 2022)
Banks are diversifying their revenue streams to include a greater proportion of non-interest- earning products. Changes in the product mix offered by banks make them more competitive and capable of generating more stable and sustainable income, which encourages banks to develop and promote new products that improve their financial performance. The increasing demand for Islamic banking products has heightened the competitive environment in the commercial banking industry, particularly in terms of the benefits of banks' product diversification strategy. Islamic banking adheres to Shariah principles, and its products are Shariah-compliant. However, there is a lack of understanding and knowledge about the specific contracts or products offered by Islamic banks. This study investigates the long-run relationship in Islamic bank financing products to improve the banks' financial performance. The financial data of sixteen Malaysian Islamic banks were gathered for this study from the Islamic Financial Services Board's Prudential and Structural Islamic Financial Indicators (PSIFIs) database (IFSB). The Autoregressive Distributed Lags (ARDL) model was used, with data spanning from 2014 to 2018. The findings revealed that Bai Bithaman Ajil, Ijarah, Musyarakah, and other Shariah-compliant products have a significant long-term impact on the performance of return on asset(ROA),financing income (RFIN), gross non-performing financing (GNPF), and net profit margin (NPM). It indicates that the financing model of Islamic banks in Malaysia is diversifying. The overall findings suggest that the diversification strategy in financing assets product may have a significant long-term impact on the financial performance of Islamic banks.